Editorial (2020)
The Universidad Santo Tomás, Seccional Tunja, presents the journal Principia Iuris No. 35, in which topics of vital importance for the legal progress are developed, conceived from the social projection, and with axiological and epistemological bases that contribute to the solution of the different problems of disciplinary and interdisciplinary investigation. The research in this edition is the development of topics that cover a great content of social and legal problems, both in a national and international context. Our journal is indexed in EBSCO, Latindex, Publindex, Google Scholar, OpenAIRE and Open Archives. In this opportunity, the Principia Iuris Journal, Series 35, presents articles that investigate and deepen in important epistemological problems, of great actuality, in the area of the philosophy of the law, public law, private law, the human rights, and the professional ethics. Therefore, the reader will find a very provocative constellation of philosophical-legal issues in this issue. As always, the permanent and inexhaustible effort of the jurists and participants of this edition is highlighted by us and, with its greatness, by the whole science of law